2022
DOI: 10.3390/jcm11133580
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Berger’s Space Development after Uneventful Cataract Surgery: Evidence from Swept-Source Optical Coherence Tomography

Abstract: Background: This study investigates the incidence and risk factors for the development of Berger’s space (BS) after uneventful phacoemulsification based on swept-source optical coherence tomography (SS-OCT). Methods: Cataractous eyes captured using qualified SS-OCT images before and after uneventful phacoemulsification cataract surgery were included. Six high-resolution cross-sectional anterior segment SS-OCT images at 30° intervals were used for BS data measurements. BS width was measured at three points on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
0
16
2
Order By: Relevance
“…Zhang et al proposed that AVD is often found contralateral to the corneal incision. 11 More importantly, granular materials were found behind the posterior lens capsule in 40.3% of cases. This high incidence has not received much attention from cataract surgeons.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Zhang et al proposed that AVD is often found contralateral to the corneal incision. 11 More importantly, granular materials were found behind the posterior lens capsule in 40.3% of cases. This high incidence has not received much attention from cataract surgeons.…”
Section: Discussionmentioning
confidence: 95%
“…8 Recently, Zhang et al reported that the incidence of AVD in phakic eyes with cataract was only 0.9%; however, the incidence of AVD was 19.7% after phacoemulsification cataract surgery. 11 Anisimova et al and Vael et al reported that the intraoperative incidence of AVD was 75.0% and 63.0%, respectively. 7,8 There were considerable differences between the studies.…”
Section: Discussionmentioning
confidence: 95%
“…13 Zhang et al visualized Berger space with SS-OCT postoperatively in 19.7% of patients who underwent uneventful phacoemulsification with no risk factors of AHD. 14 They used ultrasound power up to 40%, vacuum 500 mm Hg, and GFS to provide passive infusion at 95 to 110 cm above the eye level. The authors associated Berger space development with a higher irrigation pressure (P < .001) and shorter surgery duration (P = .021).…”
Section: Pvd = Posterior Vitreous Detachmentmentioning
confidence: 99%
“…However, in our and previous studies, despite its high incidence, no case of positive Berger space or AHD presented with AFMS, which probably means that AHD is not a sufficient condition for AFMS to occur. [14][15][16]19 Santos-Bueso evaluated the presence of the Berger space using AS-OCT in 90 patients, and he found it in 3 patients. 20 Mori et al evaluated the visibility of AHM in the retrolental space of normal human eyes, and AHM was seen in 6.9% of eyes examined with the deep-range AS-OCT. 21 In this study, postoperatively, eyes with Berger space had higher irrigation pressure and suggest that a comprehensive consideration of irrigation pressure and surgical time may better reflect the effects of cataract surgery on the vitreolenticular interface.…”
Section: Pvd = Posterior Vitreous Detachmentmentioning
confidence: 99%
“…Over the last decade, ophthalmology has significantly benefited from advances in vivo non-invasive ophthalmic imaging techniques that play currently a fundamental role in the clinical assessment, diagnosis, management, and monitoring of a wide variety of conditions involving both the anterior and posterior segment [1][2][3][4][5][6]. Imaging technologies, including anterior and posterior segment optical coherence tomography (OCT), OCT angiography, wide-field retinal imaging, specular and confocal microscopy, corneal topography, and ocular ultrasound, have dramatically improved the morphological and functional evaluation of ocular structures, both in healthy and pathological eyes [1][2][3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%